Hubungan Tahap Kematangan Emosi dan Tahap Komitmen Organisasi: Satu Kajian Kalangan Guru di Negeri Sembilan - Mohammad Razi, Azmi (2010)
The research investigates the level of emotional maturity and organisational commitment among teachers in Negeri Sembilan based on gender and their marital status. This research also studies the interrelationship between emotional maturity and organisational commitment of teachers in Negeri Sembilan. Questionnaires were distributed to 400 identified teachers that fulfilled the required variables’ criteria based on the teachers’ population in Negeri Sembilan. However, only 325 of them responded for this research. The levels of emotional maturity were measured using the Emotional Intelligence Scale (EIS) by Schutte, Malouff, Hall, Haggerty, Cooper, Golden and Dornheim (1998). Meanwhile, the levels of organisational commitment were measured using the modified instrument from British Organisational Commitment Scale (BOCS) by Cook dan Wall (1980). The Mann-Whitney U Test and Kruskal Wallis H Test were used to determine the difference levels of emotional maturity and organisational commitment based on gender and marital status. Finding shows that there are no significant differences of the levels of emotional maturity and organisational commitment between different gender and their marital status. On the other hand, Spearman’s Rho Correlation Test was used to determine the interrelationship between emotional maturity and organisational commitment of teachers in Negeri Sembilan. The correlation test shows that the interrelationship of the two variables was significant with strong positive correlation. This shows that teacher with high emotional maturity level proven to have high organisational commitment level, and vice versa, teacher with low level of emotional maturity also has low level of organisational commitment.